The Effect of Diaphragmatic Breathing Exercise on Reducing Insomnia in the Elderly - Olyverdi, Reza; Isnaini, Isnaini (Journal of Current Health Sciences, 2023)
Elderly are people who reach the age over 60 years. Along with increasing age, there will be a decrease in body function in the elderly such as excessive anxiety, decreased self-confidence, and insomnia. This study aimed to determine The Effect of Diaphragmatic Breathing Exercise to Reduce Insomnia in the Elderly in Community Health Centers of Bukittinggi, 2023. The type of study was Quasi-Experimental Design with One Group Pretest-Posttest Test. The reason for conducting this research was to find out whether there was a decrease in insomnia after being given Diaphragmatic Breathing Exercise to the elderly. The population was 20 people who attended the elderly integrated services post activities at Community Health Center Bukittinggi. By using purposive sampling, 10 people were chosen as the samples. The study was conducted for 4 weeks with the instrument was the Insomnia Severity Index. The data were analyzed by univariate and bivariate analysis by using the Wilcoxon Test. Based on the Wilcoxon Test, it showed that the p value was 0.005 less than 0.05 with an average insomnia before giving Diaphragmatic Breathing Exercise was 11.50 and after 5.20. In short, there was an effect of Diaphragmatic Breathing Exercise on Reducing Insomnia in the Elderly at Bukittinggi Community Health Centers in 2023. Abstrak: Lanjut usia adalah orang yang  mencapai usia 60 tahun ke atas. Seiring dengan bertambahnya usia, maka akan terjadi penurunan fungsi tubuh pada lansia, Kecemasan yang berlebihan, penurunan rasa percaya diri, insomnia, yang sering terlihat pada orang lanjut usia. Penelitian ini bertujuan untuk mengetahui pengaruh pemberian Diaphragmatic Breathing Exercise Terhadap Penurunan Insomnia Pada Lansia Di Puskesmas Kota Bukittinggi Tahun 2023. Jenis penelitian ini adalah Quasi-Eksperimen Design One Group Pretest-Postest Test. Alasan di lakukan penelitian ini  untuk mengetahui adanya penurunan insomnia setelah di berikan Diaphragmatic Breathing Exercise pada lansia. Populasi dalam penelitian ini sebanyak 20 orang yang hadir pada kegiatan posyandu lansia di Puskesmas Kota Bukittinggi. Teknik pengambilan sampel menggunakan metode purposive sampling sebanyak 10 orang. Penelitian dilakukan selama 4 minggu dengan isntrumen penelitian yang digunakan adalah Insomnia Saverity Index. Analisis data meliputi analisis univariat dan bivariat menggunakan uji Wilcoxon Test. Berdasarkan uji Wilcoxon Test menunjukan bahwa nilai p value 0,005 kurang dari 0,05 dengan rerata insomnia sebelum pemberian Diaphragmatic Breathing Exercise adalah 11.50 dan sesudah 5.20. Kesimpulan penelitian ini bahwa terdapat pengaruh Pemberian Diaphragmatic Breathing Exercise Terhadap Penurunan Insomnia Pada Lansia Di Puskesmas Kota Bukittinggi Tahun 2023.